A catalyst regenerable in situ, and a method for preparing and regenerating the same
Patent Information
- Application Number
- CN202611517096.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
离线高温氧化焙烧再生方法存在以下缺陷:①必须停机拆出催化剂,装置停车时间长,严重影响产能;②焙烧温度较高,极易造成贵金属纳米颗粒烧结长大,分散度永久性下降,多次再生后活性断崖式衰减;③贵金属硫化物和贵金属硫酸盐的热分解温度较高,分解速率慢,能耗高,难以保证再生效果;④蜂窝陶瓷整体式贵金属催化剂拆装过程易破损,损耗率高
(1)本发明提供的一种可原位再生的催化剂的制备方法,能够制备出具有良好再生催化活性的可原位再生的催化剂。具体的,本发明在步骤S1制备出的V-TiO2粉体,利用TiO2粉体的大比表面积,既能负载助剂钒,又能负载活性组分Pt和Pd;其中,助剂钒能够催化硫形态的转化,如促进硫化物变成硫酸盐,便于后续形成硫酸复盐;促进二氧化硫转化为三氧化硫,便于从催化体系中除去硫。此外,助剂钒除催化作用外,其在第一煅烧处理后产生的V2O5为熔融态的硫酸盐与硫酸复盐提供溶剂作用,V2O5的塔曼温度在200℃左右,当温度高于200℃(如再生时采用的温度)时,其原子扩散加强,硫酸复盐在V2O5载体上的传质效应显著增强,便于提高再生效率;TiO2粉体在还原条件下(如VOCs、CO等还原性物质),失去电子,产生Ti3+和氧空位,促进氧化反应发生;具体的,如在VOCs分子存在时,通过步骤S2引入的贵金属Pt、Pd能够促使VOCs氧化裂解产生活性氢,活性氢与TiO2粉体反应,消耗晶格氧,生成氧空位与Ti3+,Ti3+不受TiO2晶格位置束缚,在催化反应温度下发生迁移,与Pt、Pd形成Pt-O-Ti、Pd-O-Ti等界面键;如在CO分子存在时,CO吸附在Pt、Pd位点上,TiO2的晶格氧与CO反应,自身被还原形成Ti3+,继而形成Pt-O-Ti、Pd-O-Ti等界面键;Pt-O-Ti、Pd-O-Ti等界面键能够抑制贵金属氧化失活,界面电子富集使Pt、Pd活性位点维持稳定的零价金属态,有效抵御再生反应过程中的高温氧化、氧化氛围侵蚀,提升活性组分的抗氧化能力;另外,随着Pt-O-Ti、Pd-O-Ti界面键的稳固成型,能够从微观键合层面增强Pt、Pd纳米颗粒与TiO2粉体的结合力,有效抑制贵金属颗粒在高温、长周期再生反应中的迁移、团聚与烧结,保障活性位点的高分散性与长效完整性。再有,TiO2粉体耐酸性强,且几乎不与硫或二氧化硫等发生反应,避免硫中毒。本发明在步骤S1制备V-TiO2粉体时需要合理控制V与TiO2的量,当V少TiO2多时,SO2向SO3转化、亚硫酸根向硫酸根转化受限,不利于后续催化剂再生;当V多TiO2少时,TiO2的比表面积会明显减小,不适合负载,且TiO2产生的氧空位数量也会减少,催化活性会降低。进一步的,本发明在步骤S3中采用的硫酸盐溶液浸渍Pt-Pd双金属催化剂,是为了在催化剂引入低熔点的硫酸盐(如硫酸钠、硫酸钾和硫酸铯),且在硫中毒的催化剂再生时能够与贵金属硫化物和贵金属硫酸盐形成多元低共熔体系,促使贵金属硫化物和贵金属硫酸盐由固相转化为液相(如再生温度采用200~250℃和250~300℃),传质速率大大加快,离子扩散加剧,很快生成为硫酸复盐,即M2[Pt(SO4)2]或M2[Pd(SO4)2],M表示硫酸盐中的金属钠、钾和铯;在再生温度为300~400℃时,M2[Pt(SO4)2]或M2[Pd(SO4)2]受热分解为焦硫酸盐和贵金属氧化物,其中,贵金属氧化物作为再生后催化剂中的活性组分,提供催化活性;而焦硫酸盐在再生温度为400~500℃时,被分解为硫酸盐与SO3,其中,硫酸盐参与再生时与贵金属硫化物和贵金属硫酸盐形成多元低共熔体系,而SO3挥发去除,实现催化剂再生。因此,本发明组合采用步骤S1~步骤S3能够制备出具有良好再生催化活性的可原位再生的催化剂。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and in particular to a catalyst that can be regenerated in situ, and its preparation and regeneration methods. Background Technology
[0002] Noble metal catalysts (such as Pt-based, Pd-based, Rh-based, and Ru-based catalysts) are widely used in industrial fields such as catalytic oxidation of volatile organic compounds (VOCs) and CO due to their excellent low-temperature catalytic activity. However, trace amounts of sulfur-containing poisons (including H2S, SO2, COS, thiols, thiophene, and dimethyl sulfide) are commonly found in industrial feedstock gases and waste gases. Even at sulfur content levels as low as ppm or even ppb, these poisonings can still cause deactivation of noble metal catalysts, leading to shortened catalyst lifespan and increased operating costs for enterprises.
[0003] The microscopic mechanisms of sulfur poisoning deactivation in precious metal catalysts can be divided into two categories: 1) Sulfur-containing poisons in industrial feedstock gases and waste gases undergo strong chemisorption on the surface of precious metals, forming thermodynamically stable precious metal sulfides (PdS, Pd4S, PtS, and PtS2, etc.), directly blocking the catalytic active sites; 2) Sulfur-containing poisons in industrial feedstock gases and waste gases react with precious metals to form precious metal sulfates (such as platinum sulfate, palladium sulfate, platinum sulfite, and palladium sulfite, etc.), covering the surface of precious metal nanoparticles and blocking the mass transfer channels of reactants. Under normal operating conditions, precious metal sulfides and precious metal sulfates formed in the low-temperature range are difficult to decompose and are generally considered to be irreversible poisoning.
[0004] For the aforementioned situation where precious metal catalysts are prone to sulfur poisoning, common industrial solutions can be mainly divided into three categories: 1) Adding a pre-treatment device for desulfurization at the front end, such as arranging activated carbon adsorption, dry desulfurizing agents, or wet scrubbing desulfurization units upstream of the catalytic reactor, to pre-remove sulfur-containing components from the industrial feed gas and reduce the concentration of poisons. This type of solution requires regular replacement of desulfurization consumables, leading to continuously increasing operating costs; it is difficult to deeply remove trace amounts of organic sulfur; and during load fluctuations, the desulfurization unit can be penetrated by trace amounts of sulfur, which continuously enter the catalytic bed, causing slow accumulation and poisoning of the precious metal catalyst. Therefore, this type of solution can only delay the rate of sulfur poisoning of the precious metal catalyst.
[0005] 2) Develop sulfur-resistant catalysts, such as introducing oxygen storage materials like CeO2 into Al2O3 or TiO2 supports. These rare-earth oxides capture some sulfur species through oxygen vacancies, preferentially adsorbing sulfur and forming "sacrificial sites" to protect the active centers of the noble metal. However, the sulfur capacity of the oxygen storage materials used in this approach is limited. Long-term operation leads to continuous sulfate accumulation, resulting in slow poisoning of the noble metal catalyst. Therefore, this approach only slows down the sulfur poisoning rate; once sulfur accumulates to a threshold, the catalyst still becomes deactivated.
[0006] In the development of sulfur-resistant catalysts, another approach involves constructing a porous oxide shell on the outer layer of noble metal particles to sieve gas molecules and prevent sulfur species from directly contacting the active metal. However, this type of approach also hinders reactant diffusion, sacrificing catalytic activity. Over long periods of operation, sulfur species can still slowly penetrate the shell, and once poisoned, in-situ repair is impossible. Furthermore, constructing a porous oxide shell on the outer layer of noble metal particles presents challenges in terms of complex preparation processes and high difficulty in mass production.
[0007] In developing sulfur-resistant catalysts, the electronic structure of noble metals can be adjusted through noble metal alloying (such as Pt-Pd alloys and Pt-Rh alloys) to weaken the adsorption strength between the metal and sulfur. However, this approach offers limited improvement in sulfur resistance and cannot prevent the long-term accumulation of sulfur; even after deep poisoning, the catalyst is still difficult to restore its activity. Therefore, this approach can only slow down the rate of sulfur poisoning in noble metal catalysts; once sulfur accumulates to a threshold, the catalyst still becomes deactivated and lacks self-regeneration capabilities.
[0008] 3) For sulfur-poisoned precious metal catalysts, offline high-temperature oxidation roasting or offline liquid-phase regeneration methods are used to regenerate the precious metal catalysts. Specifically: The offline high-temperature oxidation roasting regeneration method requires unloading the sulfur-poisoned precious metal catalyst from the reactor and roasting it at high temperature in a muffle furnace or rotary roaster to oxidize and decompose precious metal sulfides and sulfates, allowing sulfur to desorb and be discharged as SO2. Some processes are supplemented with subsequent reduction treatment to restore the metallic precious metals. The offline high-temperature oxidation roasting regeneration method has the following drawbacks: ① It requires shutdown to remove the catalyst, resulting in long downtime and severely impacting production capacity; ② The high roasting temperature easily causes the precious metal nanoparticles to sinter and grow, permanently reducing their dispersion and leading to a precipitous decline in activity after multiple regenerations; ③ The thermal decomposition temperature of precious metal sulfides and sulfates is high, resulting in a slow decomposition rate, high energy consumption, and difficulty in guaranteeing regeneration effectiveness; ④ The honeycomb ceramic integral precious metal catalyst is easily damaged during disassembly and assembly, resulting in a high loss rate.
[0009] Offline liquid-phase regeneration methods typically involve soaking the catalyst in dilute nitric acid, hydrogen peroxide, or alkaline solutions to dissolve surface sulfates and surface sulfides. However, these methods have several drawbacks: incomplete removal of precious metal sulfides and sulfates; loss of precious metals during liquid-phase treatment; the need for subsequent drying and calcination, making the process complex; and they are completely unsuitable for in-situ regeneration within reactors and are not applicable to bulk precious metal catalysts on honeycomb carriers.
[0010] Therefore, it is necessary to provide a catalyst that can be regenerated in situ, as well as its preparation and regeneration methods, to solve the following problems: 1) solving the problem that existing anti-sulfur poisoning schemes can only delay the sulfur poisoning rate of precious metal catalysts but cannot achieve in-situ regeneration of precious metal catalysts; 2) solving the problem that existing regeneration methods can only achieve offline regeneration of sulfur-poisoned precious metal catalysts and have poor regeneration effects. Summary of the Invention
[0011] The purpose of this invention is to provide a catalyst that can be regenerated in situ, as well as its preparation and regeneration methods. The specific technical solution is as follows: In a first aspect, the present invention provides a method for preparing an in-situ regenerable catalyst, comprising: Step S1: Immerse TiO2 powder in an equal volume of vanadium oxalate solution, stir, and then let it stand. Then, take out the impregnated TiO2 powder and subject it to a first drying treatment and a first calcination treatment to obtain V-modified TiO2 powder, i.e., V-TiO2 powder. The mass of V used in the vanadium oxalate solution is 1% to 4% of the mass of the TiO2 powder; Step S2: The V-TiO2 powder is impregnated in an equal volume of impregnation solution containing Pt salt and Pd salt. After the first impregnation treatment, deionized water and binder are added to the impregnation solution to form a slurry. Subsequently, the slurry is uniformly coated on the carrier and subjected to a second drying treatment and a second calcination treatment to obtain a Pt-Pd bimetallic catalyst. The mass of Pt in the Pt salt is 0.5% to 2% of the mass of the V-TiO2 powder; The mass of Pd in the Pd salt is 0.5% to 2% of the mass of the V-TiO2 powder; Step S3: The Pt-Pd bimetallic catalyst is impregnated in a sulfate solution. After a second impregnation treatment, the Pt-Pd bimetallic catalyst is removed and then subjected to a third drying treatment to obtain a catalyst that can be regenerated in situ. The sulfate ion concentration of the sulfate solution is 0.08~0.4 mol / L; The sulfate solution includes at least one of sodium sulfate solution, potassium sulfate solution, and cesium sulfate solution.
[0012] Optionally, the second impregnation treatment uses an impregnation temperature of 20~30℃ and an impregnation time of 0.5~10min; The third drying process uses a drying temperature of 150~180℃ and a drying time of 6~8h.
[0013] Optionally, the mass ratio of Pt in the Pt salt to Pd in the Pd salt is 1:0.2~5; The Pt salt includes platinum nitrate; The Pd salt includes palladium nitrate; The first impregnation treatment uses an impregnation temperature of 20~30℃ and an impregnation time of 0.5~10min; The mass of the deionized water is 1.5 to 4 times the mass of the V-TiO2 powder; The mass of the binder is 5% to 10% of the mass of the V-TiO2 powder; The binder includes SiO2 sol; The second drying process uses a drying temperature of 110~140℃ and a drying time of 6~8h; The second calcination treatment uses a calcination temperature of 450~550℃ and a calcination time of 3~4h; The carrier includes cordierite honeycomb ceramic.
[0014] Optionally, the stirring process uses a stirring temperature of 20~30℃, a stirring time of 20~120min, and a stirring speed of 120~200rpm. The settling temperature is 20~30℃ and the settling time is 2~6h. The first drying process uses a drying temperature of 110~140℃ and a drying time of 4~6h; The first calcination treatment uses a calcination temperature of 450~550℃ and a calcination time of 2~4h.
[0015] In a second aspect, the present invention provides an in-situ regenerable catalyst, which is prepared by the method for preparing the in-situ regenerable catalyst.
[0016] Optionally, the in-situ regenerable catalyst retains ≥90% of its regenerated catalytic activity after five sulfur poisoning regeneration tests.
[0017] In a third aspect, the present invention provides a method for regenerating the in-situ regenerable catalyst, comprising: purging the sulfur-poisoned in-situ regenerable catalyst in the reactor during the original catalytic operation with hot air, and then subjecting it to gradient temperature controlled oxidation with mixed gas to obtain the regenerated in-situ regenerable catalyst. The mixed gas gradient temperature-controlled oxidation process uses a mixed gas comprising air and water vapor, wherein the partial pressure of the water vapor is controlled at 5%~15%, and the partial pressure of the air is controlled at 85%~95%; the mixed gas space velocity is 4000-6000 h⁻¹. -1 ; The mixed gas gradient temperature-controlled oxidation process includes a first temperature-controlled oxidation process, a second temperature-controlled oxidation process, a third temperature-controlled oxidation process, and a fourth temperature-controlled oxidation process, which are sequentially heated. The first temperature-controlled oxidation treatment uses a treatment temperature of 200~250℃ and a treatment time of 1.5~3h; The second temperature-controlled oxidation treatment uses a treatment temperature of 250~300℃ and a treatment time of 1~2h; The third temperature-controlled oxidation process uses a processing temperature of 300~400℃ and a processing time of 1~2 hours. The fourth temperature-controlled oxidation process uses a processing temperature of 400~500℃ and a processing time of 1~2 hours.
[0018] Optionally, the hot air purging treatment uses hot air at a temperature of 200~250℃, a purging time of 1~3 hours, and a hot air space velocity of 10000~15000 h⁻¹. -1 .
[0019] Optionally, the regeneration method of the in-situ regenerable catalyst further includes a reduction treatment after the gradient temperature controlled oxidation treatment of the mixed gas; The reduction process uses a reducing atmosphere comprising nitrogen and water vapor, wherein the partial pressure of the water vapor is controlled at 2%–5%, and the partial pressure of the nitrogen is controlled at 95%–98%; the space velocity of the reducing atmosphere is 5000–10000 h⁻¹. -1 ; The reduction process uses a reduction temperature of 300~450℃ and a reduction time of 1~4h.
[0020] Optionally, the duration of a single regeneration cycle is 8 to 12 hours.
[0021] The application of the technical solution of the present invention has at least the following beneficial effects: (1) The present invention provides a method for preparing an in-situ regenerable catalyst, which can prepare an in-situ regenerable catalyst with good regeneration catalytic activity. Specifically, the V-TiO2 powder prepared in step S1 of the present invention utilizes the large specific surface area of TiO2 powder to support both vanadium additive and active components Pt and Pd; wherein, vanadium additive can catalyze the conversion of sulfur forms, such as promoting the conversion of sulfides into sulfates, which facilitates the subsequent formation of sulfate double salts; and promoting the conversion of sulfur dioxide into sulfur trioxide, which facilitates the removal of sulfur from the catalytic system. In addition, besides its catalytic effect, the vanadium additive produces V2O5 after the first calcination treatment, which provides a solvent for molten sulfates and sulfate double salts. The Taman temperature of V2O5 is around 200℃. When the temperature is higher than 200℃ (such as the temperature used during regeneration), its atomic diffusion is enhanced, and the mass transfer effect of sulfate double salts on the V2O5 support is significantly enhanced, which facilitates the improvement of regeneration efficiency; TiO2 powder loses electrons under reducing conditions (such as reducing substances such as VOCs and CO) to produce Ti 3+ The presence of oxygen vacancies promotes oxidation reactions. Specifically, in the presence of VOCs molecules, the noble metals Pt and Pd introduced in step S2 can promote the oxidative decomposition of VOCs to produce active hydrogen. The active hydrogen reacts with TiO2 powder, consuming lattice oxygen and generating oxygen vacancies that react with TiO2. 3+ Ti 3+ Unbound by the TiO2 lattice positions, TiO2 migrates at the catalytic reaction temperature, forming interfacial bonds such as Pt-O-Ti and Pd-O-Ti with Pt and Pd. In the presence of CO molecules, CO adsorbs onto Pt and Pd sites, and the lattice oxygen of TiO2 reacts with CO, reducing itself to form TiO2. 3+This process leads to the formation of interfacial bonds such as Pt-O-Ti and Pd-O-Ti. These interfacial bonds inhibit the oxidation and deactivation of noble metals, and the enrichment of interfacial electrons maintains the active sites of Pt and Pd in a stable zero-valent metal state, effectively resisting high-temperature oxidation and oxidative atmosphere corrosion during the regeneration reaction, and enhancing the antioxidant capacity of the active components. Furthermore, the stable formation of Pt-O-Ti and Pd-O-Ti interfacial bonds strengthens the bonding force between Pt and Pd nanoparticles and TiO2 powder at the microscopic bonding level, effectively inhibiting the migration, agglomeration, and sintering of noble metal particles during high-temperature, long-cycle regeneration reactions, ensuring high dispersibility and long-term integrity of the active sites. Moreover, TiO2 powder has strong acid resistance and hardly reacts with sulfur or sulfur dioxide, avoiding sulfur poisoning. In step S1 of this invention, the amounts of V and TiO2 need to be properly controlled when preparing V-TiO2 powder. When V is low and TiO2 is high, the conversion of SO2 to SO3 and the conversion of sulfite to sulfate are limited, which is not conducive to subsequent catalyst regeneration. When V is high and TiO2 is low, the specific surface area of TiO2 will be significantly reduced, making it unsuitable for loading, and the number of oxygen vacancies generated by TiO2 will also decrease, resulting in reduced catalytic activity. Furthermore, the sulfate solution impregnation of the Pt-Pd bimetallic catalyst used in step S3 of this invention is to introduce low-melting-point sulfates (such as sodium sulfate, potassium sulfate, and cesium sulfate) into the catalyst, and to form a multi-element eutectic system with noble metal sulfides and noble metal sulfates during the regeneration of sulfur-poisoned catalysts. This promotes the transformation of noble metal sulfides and noble metal sulfates from the solid phase to the liquid phase (e.g., regeneration temperatures of 200~250℃ and 250~300℃), greatly accelerating the mass transfer rate, intensifying ion diffusion, and quickly generating sulfate double salts, i.e., M2[Pt(SO4)2] or M2[P [d(SO4)2], where M represents sodium, potassium, and cesium in the sulfate; at a regeneration temperature of 300-400℃, M2[Pt(SO4)2] or M2[Pd(SO4)2] decomposes thermally into pyrosulfate and noble metal oxides. The noble metal oxides serve as the active component in the regenerated catalyst, providing catalytic activity. At a regeneration temperature of 400-500℃, the pyrosulfate decomposes into sulfate and SO3. During regeneration, the sulfate forms a multi-component eutectic system with the noble metal sulfide and noble metal sulfate, while the SO3 volatilizes and is removed, thus regenerating the catalyst. Therefore, by combining steps S1 to S3, this invention can prepare a catalyst with good regeneration catalytic activity that can be regenerated in situ.
[0022] (2) The in-situ regenerable catalyst prepared by the present invention exhibits a regeneration catalytic activity retention rate of ≥90% after five sulfur poisoning regeneration tests, demonstrating good regeneration catalytic activity.
[0023] (3) The regeneration method provided by the present invention adopts mixed gas gradient temperature controlled oxidation treatment, which can realize the in-situ regeneration of sulfur poisoned catalyst under mild conditions. There is no need to load and unload the catalyst. The single regeneration shutdown time is shortened from the traditional 3~7 days to 8~12 hours, reducing the downtime losses caused by long-term shutdown and reducing catalyst damage caused by loading and unloading. In addition, the temperature used for regeneration in the present invention is below 500℃, which has low energy consumption and is not easy to cause active components to sinter, thus greatly extending the service life of the catalyst.
[0024] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The present invention will now be described in further detail with reference to specific embodiments. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1: A method for preparing an in-situ regenerable catalyst, comprising: Step S1: Immerse TiO2 powder in an equal volume of vanadium oxalate solution, stir, and then let it stand. Then, take out the impregnated TiO2 powder and subject it to a first drying treatment and a first calcination treatment to obtain V-modified TiO2 powder, i.e., V-TiO2 powder. The mass of V used in the vanadium oxalate solution is 1% to 4% (specifically 2%) of the mass of the TiO2 powder. Step S2: The V-TiO2 powder is impregnated in an equal volume of impregnation solution containing Pt salt and Pd salt. After the first impregnation treatment, deionized water and binder are added to the impregnation solution to form a slurry. Subsequently, the slurry is uniformly coated on the carrier and subjected to a second drying treatment and a second calcination treatment to obtain a Pt-Pd bimetallic catalyst. The mass of Pt in the Pt salt is 0.5% to 2% (specifically 1%) of the mass of the V-TiO2 powder. The mass of Pd in the Pd salt is 0.5% to 2% (specifically 1%) of the mass of the V-TiO2 powder. Step S3: The Pt-Pd bimetallic catalyst is impregnated in a sulfate solution. After a second impregnation treatment, the Pt-Pd bimetallic catalyst is removed and then subjected to a third drying treatment to obtain a catalyst that can be regenerated in situ. The sulfate ion concentration of the sulfate solution is 0.08~0.4 mol / L (specifically 0.2 mol / L). The sulfate solution includes at least one of sodium sulfate solution, potassium sulfate solution and cesium sulfate solution. In this Example 1, the sulfate solution is specifically selected as potassium sulfate solution.
[0027] The second impregnation treatment uses an impregnation temperature of 25°C and an impregnation time of 1 minute; The third drying process uses a drying temperature of 150~180℃ (specifically 160℃) and a drying time of 6~8h (specifically 6h).
[0028] The mass ratio of Pt in the Pt salt to Pd in the Pd salt is 1:0.2~5 (specifically 1:1). The Pt salt is platinum nitrate; The Pd salt is palladium nitrate; The first impregnation treatment uses an impregnation temperature of 25°C and an impregnation time of 1 minute; The mass of the deionized water is 2.5 times the mass of the V-TiO2 powder; The mass of the binder is 5% to 10% (specifically 8%) of the mass of the V-TiO2 powder. The binder is SiO2 sol; The second drying process uses a drying temperature of 120℃ and a drying time of 6 hours. The second calcination treatment uses a calcination temperature of 500℃ and a calcination time of 3 hours; The carrier is cordierite honeycomb ceramic.
[0029] The stirring process was carried out at a temperature of 25°C, a stirring time of 30 minutes, and a stirring speed of 150 rpm. The settling temperature used in the settling process is 25°C, and the settling time is 2 hours. The first drying process uses a drying temperature of 120°C and a drying time of 6 hours. The first calcination treatment uses a calcination temperature of 450℃ and a calcination time of 3 hours.
[0030] Example 2: Unlike Example 1, the sulfate solution is a cesium sulfate solution.
[0031] Example 3: Unlike Example 1, the potassium sulfate solution has a sulfate ion concentration of 0.08 mol / L.
[0032] Example 4: Unlike Example 1, the potassium sulfate solution has a sulfate ion concentration of 0.4 mol / L.
[0033] Example 5: Unlike Example 1, the mass of V used in the vanadium oxalate solution is 1% of the mass of the TiO2 powder.
[0034] Example 6: Unlike Example 1, the mass of V used in the vanadium oxalate solution is 4% of the mass of the TiO2 powder.
[0035] Comparative Example 1: Unlike Example 1, step S3 is omitted.
[0036] Comparative Example 2: Unlike Example 1, the potassium sulfate solution has a sulfate ion concentration of 0.5 mol / L.
[0037] Comparative Example 3: Unlike Example 1, step S1 is omitted, and the V-TiO2 powder in step S2 is replaced with TiO2 powder.
[0038] Comparative Example 4: Unlike Example 1, the mass of V used in the vanadium oxalate solution is 5% of the mass of the TiO2 powder.
[0039] Samples of the catalysts prepared in Examples 1-6 and Comparative Examples 1-4 were respectively loaded into a catalytic reactor for catalytic activity testing of sulfur-containing VOCs (volatile organic compounds) for 200 h. The test results are shown in Table 1. The sulfur in the sulfur-containing VOCs was H2S, with a concentration of 100 ppm and a space velocity of 15000 h⁻¹. -1 .
[0040] As shown in Table 1, the catalytic activity of each catalyst after 200 hours of catalytic activity testing was significantly lower than its initial catalytic activity, indicating that it was a catalyst poisoned by sulfur.
[0041] The sulfur-poisoned catalysts were all regenerated using the following method: Specifically, the sulfur-poisoned catalysts were purged in situ with hot air in the original catalytic reactor, and then subjected to mixed gas gradient temperature-controlled oxidation to obtain the regenerated catalysts. The mixed gas gradient temperature-controlled oxidation process uses a mixed gas comprising air and water vapor, wherein the partial pressure of the water vapor is controlled at 5%~15% (specifically 10%), and the partial pressure of the air is controlled at 85%~95% (specifically 90%); the mixed gas space velocity is 4000-6000 h⁻¹.-1 (Specifically 5000h) -1 ); The mixed gas gradient temperature-controlled oxidation process includes a first temperature-controlled oxidation process, a second temperature-controlled oxidation process, a third temperature-controlled oxidation process, and a fourth temperature-controlled oxidation process, which are sequentially heated. The first temperature-controlled oxidation treatment uses a treatment temperature of 200℃ and a treatment time of 2 hours; The second temperature-controlled oxidation treatment uses a treatment temperature of 250~300℃ (specifically 300℃) and a treatment time of 1.5h; The third temperature-controlled oxidation process uses a processing temperature of 300~400℃ (specifically 400℃) and a processing time of 1.5h. The fourth temperature-controlled oxidation process uses a processing temperature of 400~500℃ (specifically 500℃) and a processing time of 1.5h.
[0042] The hot air purging process uses hot air at a temperature of 250°C, a purging time of 1 hour, and a hot air space velocity of 10,000 h⁻¹. -1 .
[0043] The catalytic activity of each regenerated catalyst was tested using the aforementioned method, and the corresponding initial catalytic activity was recorded. This process was repeated, with each catalyst undergoing five cycles of sulfur poisoning and regeneration. The test results are shown in Table 1. In Table 1, "--" indicates that no corresponding conversion rate data was obtained.
[0044] Table 1 Catalytic activity in cycle tests (measured by conversion)
[0045] As shown in Table 1, compared with Comparative Examples 1 to 4, the catalysts prepared in Examples 1 to 6 of this invention exhibited a regeneration catalytic activity retention rate of ≥90% after five cycles of sulfur poisoning and regeneration, which is significantly better than the regeneration catalytic activity of Comparative Examples 1 to 4.
[0046] In Comparative Example 1, the Pt-Pd bimetallic catalyst was not treated with sulfate solution, which prevented the introduction of low-melting-point sulfate into the catalyst. This made it difficult to promote the formation of sulfate complex salts from noble metal sulfides and noble metal sulfates, thus hindering decomposition and reducing the regeneration catalytic activity.
[0047] In Comparative Example 2, the sulfate ion concentration in the sulfate solution used was too high, which masked the active sites of the noble metals Pt and Pd, resulting in low initial activity and low regeneration catalytic activity.
[0048] In Comparative Example 3, since V was not added, and some of the poisoning of Pt and Pd resulted in the formation of sulfides such as platinum sulfide and palladium sulfide, without V, the conversion of sulfides into sulfates could not be promoted. This part of the sulfides could not form sulfate double salts and was difficult to decompose and regenerate. Moreover, as the number of poisonings increased, the accumulation of sulfides became more severe, so the catalytic activity of the later regenerations decreased more rapidly.
[0049] In Comparative Example 4, the excessive use of V resulted in a relative reduction in TiO2 powder. In reality, TiO2 powder has a rich specific surface area and pores. Loading the active components Pt and Pd onto TiO2 results in higher activity. If they are loaded onto V2O5, the activity decreases. Therefore, both the initial activity and the regeneration catalytic activity are not high.
[0050] To compare the conventional high-temperature decomposition and regeneration method with the regeneration method protected by this invention (i.e., the regeneration method involving mixed gas gradient temperature-controlled oxidation treatment mentioned above), the catalyst prepared in Example 1 was sampled separately for five cycles of sulfur poisoning and regeneration. The test results are shown in Table 2. The regeneration method used was the conventional high-temperature decomposition method. Specifically, the sulfur-poisoned catalyst was purged in situ with hot air in the original catalytic reactor during the catalytic operation, followed by conventional high-temperature decomposition treatment to obtain the regenerated catalyst. The hot air purging treatment used a temperature of 250°C, a purging time of 1 hour, and a hot air space velocity of 10000 h⁻¹. -1 The conventional high-temperature decomposition process uses an air temperature of 700°C and a space velocity of 10,000 h⁻¹. -1 It runs continuously for 4 hours.
[0051] As shown in Table 2, compared to the conventional high-temperature decomposition and regeneration method used in Example 1, the regeneration method of this invention, which involves gradient temperature-controlled oxidation treatment with mixed gas, resulted in a catalyst regeneration catalytic activity retention rate of ≥90% after five cycles of sulfur poisoning and regeneration, significantly superior to the conventional high-temperature decomposition and regeneration method. Furthermore, while the conventional high-temperature decomposition and regeneration method showed acceptable initial regeneration results, with increasing regeneration cycles, not only did it consume enormous amounts of energy, but the sintering of precious metals also became increasingly severe. After five regeneration cycles, the efficiency dropped to 61.5%, rendering it unusable for regeneration.
[0052] Table 2 Catalytic activity (measured by conversion rate) of different regeneration methods in cyclic tests
[0053] Samples of the fresh catalyst prepared in Example 1, the catalyst after each sulfur poisoning, and the regenerated catalyst were taken for carbon and sulfur analysis. The analysis results are shown in Table 3 (Table 3 only shows the carbon and sulfur analysis results of the catalyst after the first, third, and fifth sulfur poisoning and the regenerated catalyst); the carbon and sulfur analysis was measured using the German ElementarInductar CS cube.
[0054] Table 3 Carbon and sulfur analysis results
[0055] As shown in Table 3, (1) the carbon content of the fresh catalyst prepared in Example 1, the catalyst after each sulfur poisoning, and the regenerated catalyst are all relatively low. Relatively speaking, the C content of the corresponding catalyst increases with the number of poisonings, which may be due to slight carbon deposition on the catalyst after sulfur poisoning. (2) The sulfur content of the fresh catalyst is 0.18%. This part of the sulfur is introduced due to the addition of sulfate solution during catalyst preparation in Example 1. It will not interact with the active sites and will not affect the catalytic performance. After the first sulfur poisoning, the sulfur content increased by 0.05%. This is because sulfur forms strong adsorption with Pt and / or Pd or has formed noble metal sulfides and noble metal sulfates, resulting in a decrease in catalyst performance. After the first regeneration, the sulfur content decreased to 0.18%, and the catalytic activity test results in Table 1 also show that the catalytic activity has significantly recovered. After the third sulfur poisoning, the sulfur content of the catalyst increased by 0.08% compared to the fresh catalyst and by 0.03% compared to the catalyst after the first sulfur poisoning. This indicates a strong adsorption of sulfur with Pt and / or Pd, an increase in the amount of noble metal sulfides and sulfates, or the presence of some sulfur on the support. After the third regeneration, the sulfur content of the catalyst was 0.01% higher than the fresh catalyst, indicating some residue, resulting in slightly lower catalytic activity after the third regeneration compared to the fresh catalyst. After the fifth sulfur poisoning and regeneration, the sulfur content of the catalyst was already 0.02% higher than the fresh catalyst, leading to even lower catalytic activity after the fifth regeneration compared to the third regeneration.
[0056] The above description is only a preferred embodiment of the present invention and does not limit the scope of the present invention. All equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the protection scope of the present invention.
Claims
1. A method for preparing a catalyst that can be regenerated in situ, characterized in that, include: Step S1: Immerse TiO2 powder in an equal volume of vanadium oxalate solution, stir, and then let it stand. Subsequently, the impregnated TiO2 powder was removed and subjected to a first drying treatment and a first calcination treatment in sequence to obtain V-modified TiO2 powder, namely V-TiO2 powder; The mass of V used in the vanadium oxalate solution is 1% to 4% of the mass of the TiO2 powder; Step S2: The V-TiO2 powder is impregnated in an equal volume of impregnation solution containing Pt salt and Pd salt. After the first impregnation treatment, deionized water and binder are added to the impregnation solution to form a slurry. Subsequently, the slurry was uniformly coated onto the carrier and subjected to a second drying treatment and a second calcination treatment to obtain a Pt-Pd bimetallic catalyst. The mass of Pt in the Pt salt is 0.5% to 2% of the mass of the V-TiO2 powder; The mass of Pd in the Pd salt is 0.5% to 2% of the mass of the V-TiO2 powder; Step S3: The Pt-Pd bimetallic catalyst is impregnated in a sulfate solution. After a second impregnation treatment, the Pt-Pd bimetallic catalyst is removed and then subjected to a third drying treatment to obtain a catalyst that can be regenerated in situ. The sulfate ion concentration of the sulfate solution is 0.08~0.4 mol / L; The sulfate solution includes at least one of sodium sulfate solution, potassium sulfate solution, and cesium sulfate solution.
2. The method for preparing the in-situ regenerable catalyst as described in claim 1, characterized in that, The second impregnation treatment uses an impregnation temperature of 20~30℃ and an impregnation time of 0.5~10min; The third drying process uses a drying temperature of 150~180℃ and a drying time of 6~8h.
3. The method for preparing the in-situ regenerable catalyst as described in claim 1, characterized in that, The mass ratio of Pt in the Pt salt to Pd in the Pd salt is 1:0.2~5; The Pt salt includes platinum nitrate; The Pd salt includes palladium nitrate; The first impregnation treatment uses an impregnation temperature of 20~30℃ and an impregnation time of 0.5~10min; The mass of the deionized water is 1.5 to 4 times the mass of the V-TiO2 powder; The mass of the binder is 5% to 10% of the mass of the V-TiO2 powder; The binder includes SiO2 sol; The second drying process uses a drying temperature of 110~140℃ and a drying time of 6~8h; The second calcination treatment uses a calcination temperature of 450~550℃ and a calcination time of 3~4h; The carrier includes cordierite honeycomb ceramic.
4. The method for preparing the in-situ regenerable catalyst as described in claim 1, characterized in that, The stirring process uses a stirring temperature of 20~30℃, a stirring time of 20~120min, and a stirring speed of 120~200rpm. The settling temperature is 20~30℃ and the settling time is 2~6h. The first drying process uses a drying temperature of 110~140℃ and a drying time of 4~6h; The first calcination treatment uses a calcination temperature of 450~550℃ and a calcination time of 2~4h.
5. A catalyst capable of in-situ regeneration, characterized in that, It is prepared by the method for preparing an in-situ regenerable catalyst as described in any one of claims 1 to 4.
6. The in-situ regenerable catalyst as described in claim 5, characterized in that, The in-situ regenerable catalyst retains ≥90% of its regenerated catalytic activity after five sulfur poisoning regeneration tests.
7. A method for regenerating the in-situ regenerable catalyst as described in claim 5, characterized in that, include: The in-situ regenerable catalyst after sulfur poisoning is purged in the original reactor during the catalytic operation with hot air, and then subjected to mixed gas gradient temperature controlled oxidation treatment to obtain the regenerated in-situ regenerable catalyst. The mixed gas gradient temperature-controlled oxidation process uses a mixed gas comprising air and water vapor, wherein the partial pressure of the water vapor is controlled at 5%~15%, and the partial pressure of the air is controlled at 85%~95%; the mixed gas space velocity is 4000-6000 h⁻¹. -1 ; The mixed gas gradient temperature-controlled oxidation process includes a first temperature-controlled oxidation process, a second temperature-controlled oxidation process, a third temperature-controlled oxidation process, and a fourth temperature-controlled oxidation process with sequentially increasing temperatures. The first temperature-controlled oxidation treatment uses a treatment temperature of 200~250℃ and a treatment time of 1.5~3h; The second temperature-controlled oxidation treatment uses a treatment temperature of 250~300℃ and a treatment time of 1~2h; The third temperature-controlled oxidation process uses a processing temperature of 300~400℃ and a processing time of 1~2 hours. The fourth temperature-controlled oxidation process uses a processing temperature of 400~500℃ and a processing time of 1~2 hours.
8. The method for regenerating the in-situ regenerable catalyst as described in claim 7, characterized in that, The hot air purging process uses hot air at a temperature of 200-250℃, a purging time of 1-3 hours, and a hot air space velocity of 10000-15000 h⁻¹. -1 .
9. The method for regenerating the in-situ regenerable catalyst as described in claim 7, characterized in that, It also includes a reduction treatment following the gradient temperature controlled oxidation treatment of the mixed gas; The reduction process uses a reducing atmosphere comprising nitrogen and water vapor, wherein the partial pressure of the water vapor is controlled at 2%–5%, and the partial pressure of the nitrogen is controlled at 95%–98%; the space velocity of the reducing atmosphere is 5000–10000 h⁻¹. -1 ; The reduction process uses a reduction temperature of 300~450℃ and a reduction time of 1~4h.
10. The method for regenerating the in-situ regenerable catalyst as described in claim 7, characterized in that, The duration of a single regeneration cycle is 8-12 hours.
